Menthacarin attenuates experimental colitis - Alliger, Korina; Khalil, Mohammad; König, Beatrix; Weisenburger, Sabrina; Koch, Egon; Engel, Matthias (Phytomedicine, 2020)
Background: Peppermint oil and caraway oil are established remedies in gastroenterological medicine because of their spasmolytic/analgesic effects. Purpose: We investigated whether Menthacarin, a combination of both oils, exerted anti-inflammatory effects in a dextran sodium sulphate (DSS, 2%) murine model of colitis. Study Design and Methods: C57BL/6 mice were orally administered Menthacarin in doses of 10, 30, 60, and 120 µg/g body weight (BW), and control mice received 0.2% agar, 10 µl/g BW, during 8 days of DSS-induced colitis. Colitis was monitored by BW measurements and colonoscopies. Colons of euthanised mice were excised for histological staining and ELISA measurements of the cytokines TNFα, IL-6, IL-10, IL-1β, and TGF-β. Results: Menthacarin-treated mice compared to controls showed improved macroscopical and microscopical parameters and lower BW loss during the course of colitis. Menthacarin changed the colonic cytokine profile towards a regulatory/anti-inflammatory phenotype. Conclusion: Menthacarin attenuates experimental colitis and may be a promising add-on therapy for the treatment of IBD.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Caraway; Inflammatory bowel disease; Menthacarin; Peppermint; TRPA1; TRPM8